Application of Video Tutorials as Learning Media on the Practice of Making Basic Macrame in Class X SMK Negeri 1 Sooko Mojokerto - Dwiyanti, Shifa Salsabila Ramadhani; Rahayu, Imami Arum Tri; Hidayati, Lutfiyah; Nahari, Inty (PT. Riset Press International, 2025)
Video tutorials are effective learning media in helping students' learning process because of their easy and simple use. Learning media in video tutorials makes it easier for students to understand the material and can affect their learning outcomes. The media applied is media that comes from the YouTube platform. This research aims to (1) Know the feasibility level of video tutorials in making basic Macrame and (2) Assess the learning outcomes of grade X students majoring in Fashion Management at SMK Negeri 1 Sooko Mojokerto in the practice of making basic Macrame with the help of video tutorials. This study used descriptive quantitative methods and was conducted in the odd semester. The research subjects were 33 students of class X Fashion at SMK Negeri 1 Sooko Mojokerto. The data collection method includes a video tutorial feasibility assessment and learning outcomes assessment. The research instruments are video tutorial feasibility assessment sheets and learning outcomes assessment sheets. The validators consisted of two people, namely media validators and material validators. The data analysis method used was descriptive analysis, which calculated the average level of feasibility of video tutorials and categorized learning outcomes based on KKM. The results showed that: (1) The application of video tutorials in making basic Macrame is declared feasible and can be applied in class X SMK Negeri 1 Sooko Mojokerto with a total average of 3.24, and (2) The results of the knowledge and skills assessment tests of students in class X SMK Negeri 1 Sooko Mojokerto reached an average of 85 and 90, which met the standard percentage of completeness of 100%.